PROFIL PEMBANTU PADA RUMAH TANGGA WARGA NEGARA ASING DI KOMPLEKS PERUMAHAN CPI KELURAHAN PEMATANG PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS - Septiani, Tika; Razif, M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the Village Causeway Pudu Mandau sub Bengkalis. The purpose of this study was to identify the profile of the domestic helper foreign nationals. This study entitled "Profile Domestic Helpers On Foreign Nationals". Topics focus of this research is how the maid in the household profile of foreign nationals, how the pattern of the relationship between the helper and the employer, and what are the limiting factor in domestic helper foreign nationals. The population of this study is the maid in the household of foreign nationals. Taking samples was done by simple random sampling technique. Samples were about 10 people in the household maid foreign nationals. The author uses descriptive qualitative method and the data were analyzed qualitatively. Instrument Data is observation, interviews and documentation. The results showed all respondents have a kinship patterns created by mutual respect and tolerate each other, and respondents follow cultures appreciate the time and discipline applied time employer as a basis to start any work in any field. Conclusion The results of this study indicate that all respondents came from Pekanbaru and spines in general. Respondents in generally come from poor families, the lack of job opportunities becomes a maid in the household of foreign nationals make the lives of the respondents increased. In addition, the pattern of kinship formed by itself because of the good interaction between employer and respondents in their daily life. Factors driving the respondent became a housekeeper is because his salary which could ease the burden of life, to broaden and to maintain social prestige in society.Keywords: Maid, Maid and Employer Relations pattern.